2009
DOI: 10.1063/1.3094022
|View full text |Cite
|
Sign up to set email alerts
|

Internal strains and crystal structure of the layers in AlGaN/GaN heterostructures grown on a sapphire substrate

Abstract: In this paper, we investigate the structural properties of AlGaN/GaN heterostructures grown by metal organic chemical vapor deposition on sapphire substrates with different thicknesses using high-resolution x-ray diffraction and Raman scattering methods. We discuss the microscopic nature of spatial-inhomogeneous deformations and dislocation density in the structures. Microdeformations within mosaic blocks and the sizes of regions of coherent diffraction are determined. We reveal a gradient depth distribution o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 42 publications
1
24
0
Order By: Relevance
“…42 Of these, A 1 and E 1 are both Raman and infrared active, whereas 2E 2 set ðE low 2 and E high 2 Þ are only Raman active and B 1 mode are optically silent. 12 Additionally, macroscopic electric field splits the polar A 1 and E 1 into longitudinal optical (LO) and transverse optical (TO) phonon modes. So, in the first-order Raman scattering, all of the A 1 ðLOÞ, A 1 ðTOÞ, E 1 ðLOÞ, E 1 ðTOÞ, E low 2 ; and E high 2 can be observed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…42 Of these, A 1 and E 1 are both Raman and infrared active, whereas 2E 2 set ðE low 2 and E high 2 Þ are only Raman active and B 1 mode are optically silent. 12 Additionally, macroscopic electric field splits the polar A 1 and E 1 into longitudinal optical (LO) and transverse optical (TO) phonon modes. So, in the first-order Raman scattering, all of the A 1 ðLOÞ, A 1 ðTOÞ, E 1 ðLOÞ, E 1 ðTOÞ, E low 2 ; and E high 2 can be observed.…”
Section: Resultsmentioning
confidence: 99%
“…[5][6][7][8][9][10] However, sapphire (Al 2 O 3 ) is used as a substrate for growth of III-N based epitaxial layer in spite of its larger lattice mismatch and larger thermal expansion coefficient by taking diverse growth approaches. 11,12 Notably, in these devices, AlGaN alloys are used as barrier layers, leading to excellent carrier confinement at AlGaN/GaN interface without intentional doping. [13][14][15][16][17] Generally, GaN is used as the channel material for realization of polarization induced sheet carrier concentrations at the corresponding interface.…”
Section: Introductionmentioning
confidence: 99%
“…So, there is huge interest in improving the design of nitride based LEDs and the methods of growth of nitride crystals and layers [4]. Various methods for improving of growth of nitride crystals and for decreasing the number of defects in these materials are looking for by manufacturers: the effect of surfaces and surface preparation, particularly wet and dry etching, exposure to UV light in vacuum or controlled gas ambient, annealing, and ion implantation [2,[4][5][6]. But real improvement in LED performance and reliability needs in-depth understanding the reasons of defect number growth, what leads to the migration of defects during device aging, and how these processes affect the operation characteristics and degradation of LEDs.…”
Section: Introductionmentioning
confidence: 99%
“…In previous works [3][4][5][6], it was shown that at epitaxial growth of nitride structures they relaxed by formation of dislocations and other defects also by changing of well-barrier thicknesses in SL from technological thicknesses. The deformation state, thickness fluctuation and defects in SL negatively affect on the devices performance changing their wavelength, carrier transport and carrier lifetime [7][8][9].…”
Section: Introductionmentioning
confidence: 99%